Efficient Si Nanowire Array Transfer via Bi‐Layer Structure Formation Through Metal‐Assisted Chemical Etching. (20th November 2013) - Moon, Taeho; Chen, Lin; Choi, Shinhyun; Kim, Chunjoong; Lu, Wei
<x xml:space="preserve">Abstract</x> Nanowires (NWs) have shown great potential for applications in flexible and transparent electronics. The main challenges lie in improving the transfer yield and reducing the cost of NW fabrication. Here, it is shown that a bilayer SiNW structure can spontaneously form during metal‐assisted chemical etching (MaCE). The bilayer structure formation is in turn accompanied by horizontal weak point formation that facilitates efficient nanowire transfer to diverse substrates. A mass‐transport model is developed to explain the bilayer structure and horizontal crack formation effects. Significantly, these results allow repeated SiNW etch/transfer from the same Si wafer, thus potentially greatly reducing the fabrication cost of NW‐based electronics. SiNW array‐based transistors fabricated from two sequential etch/transfer processes using a single wafer are successfully demonstrated on Si and plastic substrates.